Turning Up the Heat: 2022's Biggest Hacks. (21st November 2022) - O'Connor, Patrick
Abstract: Patrick O'Connor CISSP MBSC CEH takes a look at significant security incidents in 2022 so far: some new enemies, some new weaknesses but mostly the usual suspects.